2017
DOI: 10.1016/j.gpb.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Method Based on Information Gain and Support Vector Machine for Gene Selection in Cancer Classification

Abstract: It remains a great challenge to achieve sufficient cancer classification accuracy with the entire set of genes, due to the high dimensions, small sample size, and big noise of gene expression data. We thus proposed a hybrid gene selection method, Information Gain-Support Vector Machine (IG-SVM) in this study. IG was initially employed to filter irrelevant and redundant genes. Then, further removal of redundant genes was performed using SVM to eliminate the noise in the datasets more effectively. Finally, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…IG is a filter method that eliminates irrelevant attributes in high‐dimensional data, whereas the SVM wrapper eliminates redundancy to decrease noise in the data. The IG‐SVM method has previously shown success for biomarker selection in high‐dimensional cancer gene data …”
Section: Discussionmentioning
confidence: 99%
“…IG is a filter method that eliminates irrelevant attributes in high‐dimensional data, whereas the SVM wrapper eliminates redundancy to decrease noise in the data. The IG‐SVM method has previously shown success for biomarker selection in high‐dimensional cancer gene data …”
Section: Discussionmentioning
confidence: 99%
“…Though, Leukemia3 and Colon cancer classification performances are a bit lower compared to that of other three datasets, they are still capable to be classified with only one and two misclassifications respectively. With comparison to the study reported in [4,12], the proposed study has obtained little bit higher accuracy which is 90.47% for colon cancer dataset whereas it is 90.32% with 3 genes in former and 90.09% with 30 genes in later. Further, in the classification of colon cancer, a sparse representation based method is proposed in [3] which provide 91.94% accuracy; nevertheless with a very huge gene subset.…”
Section: B Experimental Resultsmentioning
confidence: 58%
“…The number of informative genes selected by wrapper followed by each filter is given in the parenthesis. That is, IG-EA (12) indicates that the number of elements in the gene subset selected by IG-EA for Lymphoma dataset is 12. The classification performance without gene selection and the performance with baseline classifier (i.e.…”
Section: B Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The day by day increment of cancer disease posing a serious threat to human health. The identification of the cancerous cell in the initial stage is still a challenging task, because of that the patients are diagnosed with cancer in advance stage, that increases the difficulty in the treatment of cancer [1]. Microarray is an on-chip technology, which contains the gene expression.…”
Section: Introductionmentioning
confidence: 99%